The regulation of Non-Fungible Tokens (NFTs) - El Hajjar, Ornina (2022)
Throughout the years, the world have witnessed many milestones that re-wrote history. From the industrial revolution to the creation of the first computer, every technological invention drastically changed our way of life. Each change is followed by a new law, as a way of protecting citizens. Today, we witness yet again a new revolution. The traditional internet is exceeded by the emergence of Web 3.0 and its components. New types of currencies and assets are seeing light and little or no regulations are present, which leaves a big portion of online users at threat. One of the biggest misunderstood asset is the Non-Fungible Token (NFT). First introduced as an art token, it has become one of the most prominent proof of ownership on the blockchain. Therefore, our research’s purpose is to introduce NFTs into law. It will first set forth a presentation of the new digital revolution by explaining several concepts that are crucial for the understanding of the NFT. We will then research the legal framework that can potentially be applicable to NFTs, with a focus on intellectual property as the main source for artists’ protection, and an attempt to figure out the legal aspect of NFTs according to its uses. Moreover, the research will also identify several traditional use-cases in addition to the most recent ones regarding NFTs in hope to identify where the legal standards for NFTs are heading. Finally, we will set up recommendations for a unified regulation or guideline in order to update our legal systems and keep up with the new digital uprising.